Investigating the Extent and Impact of AI Applications on Audit Firms Performance in Saudi Arabia - Othman, Mahdy S. (Journal of Ecohumanism, 2025)
This study investigates the extent and impact of AI applications on audit firm performance in Saudi Arabia, focusing on operational efficiency and audit quality in the context of Vision 2030's digital transformation agenda. Data were collected from 35 audit firms through a structured questionnaire targeting senior auditors and managers, using a two-part survey that included demographic data and variables related to AI adoption, operational efficiency, and audit quality. Descriptive statistics and regression analysis were employed to assess AI adoption levels and examine its effects. The findings reveal that AI adoption among Saudi audit firms is in its early stages, with significant variability based on firm size and technological readiness. AI positively impacts operational efficiency through task automation and predictive insights, reducing manual effort and enhancing productivity. Additionally, AI improves audit quality by reducing errors and increasing consistency. However, the results emphasize that AI’s benefits are contingent on strategic integration, proper implementation, and effective training. This research provides valuable insights for audit firms and policymakers, highlighting the transformative potential of AI in modernizing the auditing landscape and achieving Vision 2030 objectives.